IMPLEMENTATION OF COOPERATIVE LEARNING MODEL NHT TO TRAIN STUDENTS COMMUNICATION SKILL IN ACID BASE MATTER - puspitasari, lelly; Muchlis, Muchlis (JCER (Journal of Chemistry Education Research), 2021)
The aim of this research is to description the implementation of cooperative learning model NHT, students activity and practice communication skills through material of acid base. The research design used is â€œOne Shoot Case Studyâ€. Research data obtained include (1) Implementation of cooperative learning model NHT to get a score at meetings 1, 2, and 3 of 3,86, 3,90, and 3,95 with very good category. (2) The percentage of students activities that are relevant is greater than the of activities that are irrelevant. (3) Communication skills of students who are trained obtain sufficient criteria on the quantity of questions with a percentage for three consecutive meetings of 25%; 44,44%; and 55,56% and the quantity of opinion students get a good assessment criteria of 41,67%; 61,11%; and 75%. On the quality of asking students get an excellent title for three consecutive meetings 8,33%; 11,11%; and 25% and the quality of opinion students of 5,56%; 25%; and 27,78%.